Nature tourism trends in Australia with reference to the Greater Blue Mountains World Heritage Area. Issue 6 (3rd June 2017) - Hardiman, Nigel; Burgin, Shelley
ABSTRACT: Nature-based tourism has been viewed as a large and growing segment of the tourism market. Advocates of nature-based tourism argue its potential to generate income for biodiversity conservation and local economic benefit, while detractors fear a risk of "loving our parks to death". Some recent studies have suggested that nature-based tourism may be declining on a per capita basis, especially in economically developed countries. Others have detected no such trend. Nature-based tourism is a key industry within Australia, based strongly on its unique scenery and biodiversity. We compared nature-based visitation and population growth during 1998–2012 for Australia overall and specifically for the Greater Blue Mountains World Heritage Area which is adjacent to the country's largest conurbation of Greater Sydney. We found substantial declines in domestic per capita visitation, both nationally and regionally. Because visitation provides the "political capital" for parks to survive, strategies to encourage visitation should be a target for land managers. Since children foster environmentally responsible behaviour in adults, they should be part of the focus for developing diverse experiences that encourage park visitation.